2021
DOI: 10.3390/ijms22168391
|View full text |Cite
|
Sign up to set email alerts
|

CDK4, CDK6/cyclin-D1 Complex Inhibition and Radiotherapy for Cancer Control: A Role for Autophagy

Abstract: The expanding clinical application of CDK4- and CDK6-inhibiting drugs in the managements of breast cancer has raised a great interest in testing these drugs in other neoplasms. The potential of combining these drugs with other therapeutic approaches seems to be an interesting work-ground to explore. Even though a potential integration of CDK4 and CDK6 inhibitors with radiotherapy (RT) has been hypothesized, this kind of approach has not been sufficiently pursued, neither in preclinical nor in clinical studies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 96 publications
(150 reference statements)
0
11
0
Order By: Relevance
“…The activities of cyclin dependent kinases 4 and 6 (CDK4 and CDK6) are also essential to the cell cycle. They form a complex with cyclin D1 to jointly regulate tumor proliferation, and this complex is becoming a new target for tumor therapy ( 23 , 24 ). Previous studies have reported that the knockdown of PIMREG can inhibit the proliferation of prostate cancer, glioma and breast cancer cells by prolonging G1 cell phase ( 9 , 13 , 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…The activities of cyclin dependent kinases 4 and 6 (CDK4 and CDK6) are also essential to the cell cycle. They form a complex with cyclin D1 to jointly regulate tumor proliferation, and this complex is becoming a new target for tumor therapy ( 23 , 24 ). Previous studies have reported that the knockdown of PIMREG can inhibit the proliferation of prostate cancer, glioma and breast cancer cells by prolonging G1 cell phase ( 9 , 13 , 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…CDK, cyclin-dependent protein kinase, is a group of serine/threonine protein kinases [ 33 ]. CDK drives the cell cycle through chemotaxis on serine/threonine proteins and acts synergistically with cyclin, an important factor in cell cycle regulation, and CDK4 is an important isoform in the family [ 34 ]. A large number of studies have found that drugs can inhibit the growth of tumor cells by suppressing the expression of cyclins such as CCND1 and CDK4.…”
Section: Discussionmentioning
confidence: 99%
“…CDK6 (cyclin-dependent kinases 6), could form complexes D-type cyclins (D1, D2 and D3) and progress cells to early G1 phase (22). CDK4/6-cyclin D complexes is regulated by Cip/Kip proteins which had impacted on nuclear translocation of complexes (23,24). Some researches had reported that overexpression of CDK6 could affect on lymphoma, leukemia and other malignancies.…”
Section: Discussionmentioning
confidence: 99%